Combined effects of a circuit training programme and Honey supplementation on bone metabolism markers in young males - Aziz, Azlina (2011)
INTRODUCTION: Besides physical activity, bone health can be enhanced and maintained through adequate nutritional intake in prevention of osteoporosis. To date, little is known about the combination effects of a circuit training programme and honey supplementation on bone health in young males. PURPOSE: This study was carried out to investigate the effects of 6 weeks combined circuit training and honey supplementation on bone metabolism markers in young males. METHODS: Forty young male subjects (Age: 19 to 25 years old) were assigned into four groups, with ten subjects per group (n=10): sedentary without honey supplementation control (C), sedentary with honey supplementation (H), circuit training without honey supplementation (Ex), circuit training with honey supplementation (HEx) groups. Circuit training consisted of one hour per session, three times per week for six weeks. Subjects in Hand HEx consumed 300mL ofTualang honey drink containing 20g of honey for 7 days per week. Subjects in HEx consumed honey drink 30 minutes before performing circuit training. Immediately before and after six weeks of experimental period, subject's anthropometry parameters were measured and blood samples were taken in order to measure concentrations of serum alkaline phosphatase (ALP), serum osteocalcin as bone formation marker, and serum C-terminal telopeptide of type 1 collagen (1 CTP) as bone resorption marker. RESULTS: At post test, the combination of circuit training and honey supplementation (HEx) was found significantly (p<0.05) increased serum alkaline phosphatase (bone formation). Meanwhile, significant (p<0.05) reduction in serum 1 CTP (bone resorption) was found in both H group and HEx group at post test compared to their pre test value respectively. CONCLUSION: The results of present study suggests that combination of circuit training and honey supplementation elicit more beneficial effects on bone health generally compared to circuit training or honey supplementation alone in young males subjects.